A revíziós gondolat és a területgyarapodás a „Kecskeméti Lapok" hasábjain - Miklós, Péter (Közép-Európai Közlemények, 2016)
In this study the author presents the questions of the revisionist ideas and the territoral accession in the columns of ’Kecskeméti Lapok’ (Kecskemét Papers). The ’Kecskeméti Lapok’ was the best known media product in the hungarian city, Kecskemét in the period of the Horthy-age. The ideological principle of the editors of the paper was the christian national idea in that time. The articles criticized the peace treaty of Trianon and celebrated the revisional successes. The sources of this essay the newspaper ’Kecskeméti Lapok’, published between 1920 and 1941.